Improving Public Sector Service Quality, Public Trust, And Responding To Change In The Public Sector Through Marketing Strategies : A Systematic Literature Review: Improving Public Sector Service Quality, Public Trust, And Responding To Change In The Public Sector Through Marketing Strategies : A Systematic Literature Review - Umpain, Siti Hatijah; Herachwati, Nuri; Faruq, M. (Universitas 17 Agustus 1945 Surabaya, 2024)
In the public sector's modernization process, advances in ICTs play a pivotal role. The government's ability to succeed during times of change hinges on providing high-quality services and maintaining public trust. Effective marketing strategies and IT implementation can significantly enhance the efficiency, accessibility, and public perception of public services. Through a Systematic Literature Review (SLR), this study investigates the literature on marketing strategies, governance, public services, trust, and organizational change in the public sector. 10 articles identified through Publish or Perish met the research criteria and provided thematic and quantitative analyzes to substantiate the findings. This review underscores the potent role of information technology and persuasive marketing in enhancing service quality and bolstering public trust. The data collected reveals that governments employ technological innovations to improve services and overcome challenges. Coordinating IT and marketing strategies in the public sector improves service quality, builds public trust, and increases flexibility. Creating effective marketing plans and maximizing IT spending can significantly enhance operational effectiveness, build a positive public service reputation, and ultimately lead to increased public confidence and adaptability. Keywords: Service Quality, Public Trust, Response to Change, Public Sector, Marketing Strategies